A novel postgraduate endoscopic course using a large animal model of secondary Crohn's disease stricture - Lukas, Martin; Kolar, Martin; Ryska, Ondrej; Juhas, Stefan; Juhasova, Jana; Kalvach, Jaroslav; Pazin, Jaroslav; Kocisova, Tereza; Foltán, Ondřej; Kristianova, Hana; Ptacnik, Jan; Vitkova, Ivana; et al. (Surgical endoscopy, 2021)
BACKGROUND: The increasing complexity of advanced endoscopic techniques places a high demand on the endoscopist's expertise. Thus, live porcine models have been more frequently used for training. We briefly describe a hands-on postgraduate endoscopic course regarding a novel method of treatment of anastomotic strictures in a porcine model. METHODS: The porcine model of Crohn's disease anastomotic stricture with two artificial side-to-side ileo-colonic anastomoses was used. Participants performed endoscopic stricturotomy under supervision at one of two equipped endoscopic stations. Available animals were endoscopically re-examined 3 months after the course. RESULTS: Twelve anastomoses were prepared for the course. Eleven circumferential stricturotomies together with horizontal cut and clip placement were conducted. All anastomoses were passable for the scope after the procedure, and no case of perforation or bleeding occurred. All anastomoses available for re-examination remained passable for the endoscope after 3 months. CONCLUSION: We successfully organised the first endoscopic hands-on course for the training of endoscopic stricturotomy on a large animal model.
Keywords: dilatace; Animals; Humans; Crohnova nemoc; lidé; Crohn Disease; zvířata; Dilatation; modely nemocí na zvířatech; prasata; Constriction, Pathologic; Swine; stenóza; Treatment Outcome; výsledek terapie; Disease Models, Animal